Coating of TIG-welded micro-alloyed 38MnVS6 steel with flux-cored wire and FeB addition: microstructure, hardness, and wear properties - Kaptanoglu, Mustafa; Odabasi, Akin (Walter de Gruyter Gmbh, 2025)
In this study, coating deposition processes were carried out by the TIG welding technique using Magmaweld FCO-540 flux-cored wire and ferroboron (FeB) additive to improve the surface properties and service life of micro-alloyed 38MnVS6 steel. Microstructure determination, chemical composition analyses, hardness measurement, and wear tests characterized the coatings obtained. End of the characterization processes, it was determined that there were complex carbide structures consisting of various alloying elements in the coating microstructures and these structures transform into carbides and boro-carbides and borides morphology depending on the increasing amount of ferroboron. Similarly, thanks to the use of flux-cored wire and increasing rates of FeB, the amount of alloying elements in the coatings increased and this increase caused the hardness values from 59 to 65 HRC. Besides, reductions in wear losses were determined inversely proportional to the hardness results, depending on the flux-cored wire and the increased FeB amounts. However, due to the presence of macro-size cracks in #4 and #5 samples with the highest hardness values, it has been determined that the usability of these coatings in practice is limited and there is no obstacle to the use of other coatings.
Keywords: 38MnVS6 steel; ferroboron; coating; flux-cored wire; TIG welding